Endophytic microorganisms from coffee tissues as plant growth promoters and biocontrol agents of coffee leaf rust - Silva, Harllen S. A.; Tozzi, Joao P. L.; Terrasan, Cesar R. F. [UNESP]; Bettiol, Wagner (Academic Press Inc. Elsevier B.V., 2012)
A total of 234 strains of endophytic bacteria (217) and fungi (17) from coffee tissues were evaluated for their potential to control coffee leaf rust (Hemileia vastatrix) and to promote the growth of coffee seedlings. None of the fungal strains induced plant growth or reduced disease severity. Bacterial strains 85G (Escherichia fergusonii), 161G, 163G, 160G, 150G (Acinetobacter calcoaceticus) and 109G (Salmonella enterica) increased plant growth; the maximum increase was induced by strain 85G. This strain in vitro produced phosphatase and indol acetic acid. In an exploratory assay to control rust on coffee leaf discs, nine bacterial strains: 64R, 137G, 3F (Brevibacillus choshinensis), 14F (S. enterica), 36F (Pectobacterium carotovorum), 109G (Bacillus megaterium), 115G (Microbacterium testaceum), 116G and 119G (Cedecea davisae) significantly reduced disease severity when applied 72 or 24 h before challenging with the pathogen. Strains 3F, 14F, 109G, 115G, 119G, and 137G significantly reduced the severity of coffee leaf rust when compared to the diseased control in the seedling assay, when applied 72 h before challenging with the pathogen. Strain 109G was the most effective in this assay. Urediniospore germination was reduced 66% by strain 3F. There was no correspondence between the organisms that promoted seedling growth and those that reduced coffee leaf rust severity on seedlings or leaf discs. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Endophytic bacteria; Endophytic fungi; Growth promotion; Coffea arabica; Hemileia vastatrix